THE EFFECT OF THE DEMOGRAPHIC BONUS, DEPENDENCY RATIO, AND LABOR FORCE PARTICIPATION RATE ON ECONOMIC GROWTH IN EAST JAVA PROVINCE - Kusmita, Yeni; Mutmainnah, Mutmainnah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
Success in economic development can be seen from economic growth because economic growth is an important indicator to measure the success of a country's development. Population growth, and its consequences on the increase in the number of labor force, has been seen as a positive factor to encourage economic growth. The purpose of this study is to describe: 1) the effect of demographic bonus on economic growth in East Java province. 2) the effect of dependency ratio on economic growth in East Java province. 3) the effect of labor force participation rate on economic growth in East Java province. 4) the effect of demographic bonus, dependency ratio, and labor force participation rate on economic growth in East Java province. This type of research is quantitative research using panel data regression analysis method. The sampling technique in the study uses Non-Probability Sampling with saturated sampling technique. Saturated sampling is a technique that involves all members of the population as samples that are used as research objects, with individual unit observations of 29 Regencies and 9 Cities in East Java Province in a five-year period from 2019 to 2023. The results of this study indicate that partially the Demographic Bonus variable (X1) partially has a significant influence on Economic Growth in East Java Province, the Dependency Ratio variable (X2) partially does not have a significant influence on Economic Growth in East Java Province, the Labor Force Participation Rate variable (X3) partially has a significant influence on Economic Growth in East Java Province, Based on the results of the study, it states that the demographic bonus, dependency ratio, and TPAK have a simultaneous impact on economic growth in East Java province.